Carbon sequestration in back‐barrier tidal marsh soils. Issue 5 (15th July 2022) - Stolt, Mark; Hardy, Amber
Abstract: Tidal marshes are broad flat wetlands that have some of the highest carbon stocks of any ecosystem. Although the amount of carbon stored in these soils is undeniable, there are a number of uncertainties regarding carbon sequestration rates of these systems. One of the timeliest is related to the usefulness of a single sequestration rate for carbon accounting purposes. We measured soil organic carbon (SOC) sequestration rates across an elevation gradient in three back‐barrier tidal marshes in New England to test if a single sequestration value can be used for such marshes. Time zero was marked by deposition of overwash sediments from Hurricane Sandy in 2012. A total of 52 sampling locations were established at the three marshes. Eight years after overwash deposition, average plant cover ranged from 55 to 94%. Soils developed thin A horizons over underlying overwash C horizons. Sequestration rates ranged from 52 to 637 g carbon m −2  yr −1 . These rates are three to four times that of the average SOC sequestration rate in New England forests. Sequestration rates increased as elevation decreased ( p values were .006, .020, and .16 for the three marshes). Average SOC sequestration rates for the lowest elevation marshes (296 and 326 g m −2  yr −1 ) were significantly higher than that of the higher elevation marsh (186 g m −2  yr −1 ). Our studies suggest that there is a significant elevation relationship in carbon sequestration within marshes, and a single sequestration rate is not representative of all marshes in similar settings. Core Ideas: Back‐barrier tidal marsh soils sequester three to four times more carbon than upland forest soils. In part, elevation above sea level controls carbon sequestration rates. Carbon sequestration rates vary significantly within and among tidal marshes of similar settings.